The association between atopic dermatitis and cellulitis: a case report and literature review - Odeyinka, Abiola Z.; Khan, Ali (International Journal of Research in Dermatology, 2025)
There are numerous racial and ethnic differences in atopic dermatitis (AD) morphology, distributions, texture, and pigmentation that make diagnosing AD challenging across Fitzpatrick skin types. This incredibly complex pathophysiology involves interactions between the innate and adaptive immune system, keratinocytes and sensory nerve cells. When patients attend busy clinic setting, dermatologists frequently have insufficient time to educate patients adequately regarding the multiple factors that are important in managing AD. Management involves parental and patient education as well as pharmacological management such as topical creams, calcineurin inhibitors (cyclosporine), methotrexate, azathioprine, mycophenolate mofetil and newer targeted therapies like dupilumab and JAK inhibitors. Recurrent bacterial skin infections and lichenification are typically associated with moderate to severe AD. Staphylococcus aureus is a gram positive, beta-hemolytic, catalase positive, coagulase positive cocci occurring in clusters. This organism has a predilection for skin (stratum corneum), heart, and the joints. Dupilumab is a new biologic therapy approved by the food and drugs administration (FDA) for the treatment of moderate- severe AD. It blocks the IL-4 and IL-13 signaling, which are key cytokines driving inflammation in AD.